Systemic Immune Response to Traumatic CNS Injuries—Are Extracellular Vesicles the Missing Link? - Yates, Abi G.; Anthony, Daniel C.; Ruitenberg, Marc J.; Couch, Yvonne (Frontiers in Immunology, 2019)
Inflammation following traumatic injury to the central nervous system (CNS) persists long after the primary insult and is known to exacerbate cell death and worsen functional outcomes. Therapeutic interventions targeting this inflammation have been unsuccessful, which has been attributed to poor bioavailability owing to the presence of blood-CNS barrier. Recent studies have shown that the magnitude of the CNS inflammatory response is dependent on systemic inflammatory events. The acute phase response (APR) to brain injury presents an alternative strategy to modulating the secondary phase of CNS injury. However, the communication pathways between the CNS and the periphery remain poorly understood. Extracellular vesicles (EVs) are membrane bound nanoparticles that are regulators of intercellular communication. They are shed from cells of the CNS including microglia, astrocytes, neurons and endothelial cells, and are able to cross the blood-CNS barrier, thus providing an attractive candidate for initiating the APR after acute CNS injury. The purpose of this review is to summarise the current evidence that EVs play a critical role in the APR following CNS injuries.